An Experimental Study of the Impact of Aging on Gilsonite and Trinidad Epuré Modified Asphalt Binders Properties - Słowik, Mieczysław; Bilski, Marcin (The Baltic Journal of Road and Bridge Engineering, 2017)
The tests and analyses presented in the paper are related to the 20/30, 35/50 and 50/70 penetration grade road bitumens as well as the asphalt binders obtained through modification of the 35/50 and 50/70 bitumens. The latter were modified by adding to it 3%, 5% and 7% of the Gilsonite natural asphalt and 15%, 25% and 35% of the Trinidad Epuré Z 0/8 natural asphalt. The aim of the study was to assess the changes in the functional and rheological properties of the road bitumens that were modified by adding to them the Gilsonite and Trinidad Epuré natural asphalts. The modified asphalt binders were subjected to the laboratory simulated short-term and long-term aging, where two methods, designed as part of the Strategic Highway Research Program, were used, i.e. the Rolling Thin Film Oven Test and the Pressure Aging Vessel, respectively. The study of the asphalt binders both those that were subjected to aging and those unaged includes thermal susceptibility (the Penetration Index) and resistance to cracking at low temperatures by tests carried out using the Bending Beam Rheometer. The analysis of the results revealed that the unfavourable impact of the aging process on the asphalt binder properties is limited if a suitable amount of the natural asphalt is used as a modifier.